Rehabilitation in dysfunctions of temporomandibular joints - Dąbrowska, Maria; Paruszewska-Achtel, Monika; Lisiecki, Jakub; Biernacki, Maciej; Ulenberg, Agata; Ulenberg, Grzegorz (Journal of Education, Health and Sport, 2019)
The treatment of the temporomandibular joints dysfunctions shall be complex due to several possible causes that trigger the disorders. Rehabilitation is based on adopting the techniques that originate from manual therapy, applying physiotherapy, classical and transverse massage, as well as autotherapy. Moreover, in the course of the therapy, Kinesio taping, post-isometric relaxation, positional release, release and rolling of the skin are also applied. Cooperating with an orthodontist, a stomatologist, a physiotherapist and a psychologist, as well as the commitment to the treatment on the part of the patient shall allow the cure to take effect in the joint itself and the muscles surrounding it.